(Re)donner sens. Autorité et autoréflexivité de l’archive visuelle d’exposition à des fins curatoriales - Hoffsummer, Camille (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2026)
While artistic and curatorial practices based on the appropriation of museum archives are regularly associated with the methods of certain conceptual artists, and particularly with those engaged in institutional critique, their expansion to an institutional level within museums is nonetheless non-existent. The emergence of these so-called «appropriationist» practices in the 1970s appears to have been informed by the critical re-reading by certain museums of the conditions under which their collections are presented. Drawing on the case of the Van Abbemuseum in Eindhoven (Netherlands), this article considers the status, new uses and re-semiotization of the visual exhibition archive through the re-enacting of past exhibitions.